The Significance of Inclusion Concept in the Educational System as Perceived by Junior Secondary School Teachers: Implications for Teacher Training Programmes in Botswana - Adedoyin, O.; Okere, E. (Global Journal of Social Sciences Studies, 2017)
This is a quantitative study on Botswana Junior Secondary School teachers’ perceptions of the significance of inclusion concept in the educational system. A questionnaire on inclusion concept was developed on a four likert scale and administered to a stratified random sample of 100 teachers in 10 CJSS schools in Gaborone. Out of which 81CJSS teachers responded to the questionnaire and their responses were coded, analysed using descriptive statistics ( frequencies, means and standard deviations). Independent t-test and ANOVA were used to find if there were any significant differences in the teachers’ perceptions with respect to gender and years of experience of CJSS teachers on the concept of inclusion in the educational system. The main findings for this study in general revealed that teachers have positive perceptions towards the concept of inclusion in the educational system. The findings also revealed significant differences with respect to gender of teachers and years of experience on their perceptions towards the significance of the concept of inclusion in Botswana educational system. The findings of this study have significant implications to the school administrators, teachers and other stakeholders who are directly and indirectly involved in implementing inclusive education in Botswana.